Preconceptions of policies, strategies, and challenges in education 5.0 - Albattat, Ahmad; Azar, Ali Sorayyaei; Hassan, Viana; Valeri, Marco (IGI Global, 2024)
In the era of Education 5.0, institutions face a pressing challenge: aligning educational policies and practices with the rapidly evolving demands of a digital, interconnected world. This transformation requires a fundamental shift in thinking that encompasses not only the content of education but also the methods and strategies used to impart knowledge. Issues of inclusivity and the digital divide, which threaten to widen existing gaps in access and quality, magnify this task. Preconceptions of Policies, Strategies, and Challenges in Education 5.0 offers a comprehensive solution to these pressing issues. By delving into the transformative landscape of education, this book provides a roadmap for policymakers, educators, and institutions to navigate the complexities of the 5.0 era. Through carefully analyzing policies, competencies, strategies, directions, and challenges, the book offers valuable insights into how education can adapt and thrive in the digital age.